Xanthine oxidoreductase activity in MASLD: links to lipid metabolism, oxidative stress, and inflammation - Cen, Yangyang; Pu, Zhiyu; Zi, Xuanxuan; Peng, Shenglin; Liu, Ruihan; Yang, Bowen; Fan, Yanna; Yang, Jianjun; Zhao, Yi; Zhang, Yannan (Frontiers in Endocrinology, 2026)
AimsTo evaluate the differences in xanthine oxidoreductase (XOR) activity, metabolomic profiles, markers of oxidative stress, and inflammatory factors between patients with metabolic dysfunction-associated steatotic liver disease (MASLD) and healthy controls, as well as the correlations among these factors.MethodsA case-control study was conducted involving 54 MASLD patients alongside 54 healthy controls who were matched for age, gender, and ethnicity. Participants underwent comprehensive blood biochemical testing, including liver function, kidney function, glucose, lipid, XOR activity, markers of oxidative stress, and inflammatory factors. Non-targeted metabolomics detection was conducted to identify alterations in the metabolites of MASLD patients.ResultsMASLD patients showed significantly elevated levels of XOR activity, and this increase was positively correlated with significantly altered markers of oxidative stress and inflammatory factors, including increased malondialdehyde levels, tumor necrosis factor-α and interleukin-6. Metabolomic analysis revealed a unique pattern of specific metabolites, including animo acids, sphingolipids, phospholipids, and fatty acids, which were significantly altered in MASLD. A total of 100 metabolites were identified as differentially expressed between MASLD and control groups, with 44 metabolites specifically associated with XOR activity. These metabolites were significantly correlated with lipid profiles, oxidative stress indices, and inflammatory factors.ConclusionThis study demonstrates significant alterations in XOR activity, lipid metabolism, oxidative stress, and inflammatory reactions in MASLD, as well as the significant association between these factors.